Associations of physical activity and sedentary behavior with appetite sensations and eating regulation behaviors before and during the initial year following bariatric surgery. (2nd September 2021) - Bond, Dale S.; Smith, Kathryn E.; Schumacher, Leah M.; Vithiananthan, Sivamainthan; Jones, Daniel B.; Webster, Jennifer; Thomas, J. Graham
Abstract: Background: Bariatric surgery produces weight loss in part by impacting appetite and eating behavior. Research suggests physical activity (PA) assists with regulation of appetite and eating during non‐surgical weight loss, although whether PA carries similar benefits in the context of bariatric surgery is unknown. Objective: Evaluate associations of moderate‐to‐vigorous intensity PA (MVPA) and sedentary time (ST) with appetite sensations (hunger [homeostatic/hedonic], satiety) and eating regulation behaviors (restraint, disinhibition) before and during the initial year following bariatric surgery. Method: Adult bariatric patients received an accelerometer to measure MVPA/ST and a smartphone to complete appetite/eating ratings at four semi‐random times daily for 10 days at pre‐ and 3‐, 6‐, and 12‐months post‐surgery. Data were analyzed using generalized linear mixed models. Results: Higher MVPA levels related to more satiety across time ( p  = 0.045) and more restraint at 3‐months post‐surgery ( p  < 0.001). At pre‐surgery, higher MVPA levels also related to more disinhibition ( p 's < 0.01), although participants reported more disinhibition on days they performed less MVPA than usual ( p  = 0.017). MVPA did not relate to hunger. Lower ST levels related to more hedonic hunger ( p  = 0.003), especially at 12‐months post‐surgery ( p  < 0.001), and participants reported more homeostatic hunger on days they accumulated more ST than usual ( p  = 0.044). Additionally, higher ST levels related to more disinhibition at 3‐months post‐surgery ( p 's < 0.01) and lower restraint at pre‐surgery ( p 's < 0.05). ST did not relate to satiety. Conclusions: This study is the first to show that MVPA and ST each associate with appetite and eating regulation in daily life before and during post‐surgical weight loss. Results, while preliminary and requiring experimental confirmation, highlight potential for targeting bariatric patients' activity behaviors to enhance modulation of appetite, control of food intake, and resistance to overeating.